Conservation Status of the Masked Bobwhite in Sonora, Mexico - David García-Solórzano; Edgardo López-González; Carlos González-Rebeles Islas (National Quail Symposium Proceedings, 2017)
The historical distribution of the endangered masked bobwhite (Colinus virginianus ridgwayi) ranged from southern Arizona, United States, to Central Sonora, Mexico. Research in Sonora the past 30 years focused on the largest known populations, near the town of Benjamin Hill on the El Carrizo ranch. Research and perceptions by local residents pointed to a decline in masked bobwhite over the past decade. We evaluated existence of the subspecies during 2013-15 by searching transects and interviewing local residents. Our evaluation yielded no validated observations of masked bobwhite, and subsequently we call for further coordinated population monitoring and the development of technology to identify vocalizations by the subspecies.
Keywords: conservation status; endangered species; colinus virginianus ridgwayi; masked bobwhite; Mexico; Sonora